Testicular Biometric Parameters and their Association with Body Weight in Stray Dog (Canis familiaris) of Junagadh, Gujarat - M Gadariya, Gayatri; Kumar, Vishnudeo; Sharma, Anil; H Bhatt, Raghuvir; J Padodara, Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present investigation was undertaken to examine testicular biometry parameters and their association with body weight in stray dogs.  The study was conducted on testes of 18 adult, apparently healthy dogs captured and operated for sterilization at the Veterinary Hospital  of Junagadh Municipal Corporation, Ivanagar, Junagadh. The testicular weight, volume, length, width, thickness and circumference  were measured and examined. The testicular parameters did not differ significantly (p>0.05) between left and right testis. A high and  positive association, r-values being 0.432 to 0.989, was estimated among testicular parameters, viz., length, width, thickness, weight  and volume of testis. However, the association of body weight with these testicular biometry parameters was non-significant (p>0.05),  the values being negative, low to medium in magnitude, ranging from -0.096 to -0.386.
Keywords: Biometry; Correlation; Dog; Testis